A Way Forward for A Greener Future - Sustainability in Oral Health Care - Hephzibah Blessy Jangili; Navya Vyas (Medsci Publications, 2023)
Oral health professionals promote universal oral health for diseases that are primarily preventable and/or treated in their early stages. The delivery of oral health care, whether through therapeutic interventions, preventive care, or long-term maintenance, causes pollutants and has a significant carbon footprint. Oral health practitioners share a moral obligation to society to offer optimal oral health services, ensure patient safety, and decrease their environmental impact. To ensure the long-term viability of oral healthcare services, all organisations should recognise the critical need to work together to develop knowledge, identify remedial possibilities, and exchange best practices that are environmentally friendly.